STRATEGI PEMASARAN UNTUK MENINGKATKAN OMZET PENJUALAN PADA TOKO DUO SISTER HIJAB KOTA BENGKULU - Murti, Annisa; Ekowati, Sri (Yayasan Insani Mandiri Santani, 2020)
Sister Duo Hijab store is a company engaged in fashion which produces and markets hijab, clothes, pants, hijab shirts, tuspins etc. This business has been running for 3 years and is growing well but has many competitors in the same field. This study is entitled